Factors Affecting the Recognition of International Opportunities by SME Entrepreneurs: Case Studies from the Creative Industries in Indonesia - Astuti, Novika Candra; Sakti, Intan Widuri; Suhardi, Agatha Rinta; Sari, Oktora Yogi; Oktaviani, Desy; Darajat, Zakiah (ASEAN Marketing Journal, 2024)
Manuscript type: Qualitative paper Research aims: To explore the factors influencing the recognition of international opportunities among entrepreneurs in emerging markets, focusing on small and medium-sized enterprises (SMEs). Design/methodology/approach: This study employs multiple case studies, investigating six Indone- sian SMEs in the creative industries. Research Findings: Entrepreneurs often recognize international opportunities through serendipi- tous events such as encounters with local agents, communications with foreign clients via Google Ads/Facebook Ads, invitations from government entities, and referrals from acquaintances. These international opportunities are often acknowledged based on prior business experience from initial internationalization, the use of social and business networks, and digital marketing strategies. While initial expansion into the global market was impromptu, subsequent entries became deliberate strate- gies involving social and business networks, previous international experience, and digital marketing platforms such as TikTok Shop, Facebook, and Instagram. Theoretical Contribution/Originality: This study provides a comprehensive understanding of how SMEs in emerging markets recognize international opportunities, emphasizing the role of serendipi- tous events and digital marketing in the internationalization process. practitioner/policy Implication: Policymakers and practitioners should support SMEs in leverag- ing digital marketing platforms and building strong social and business networks to enhance their recognition and pursuit of international opportunities. Research limitation/Implications: The study is limited to Indonesian SMEs in the creative indus- tries, which may impact the generalizability of the findings. Future research could investigate similar dynamics in other sectors and emerging markets to validate and extend these insights.